Balancing Innovation and Equity: an Analysis of the European AI Act - Pappagallo, Sergio (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
This section illustrates the regulatory logic of the European AI Act, Regulation (EU) 2024/1689, providing a systematic introduction through the precautionary principle framework. The analysis begins with the artificial intelligence definition contained in Article 3, highlighting the technical and philosophical criticalities characterizing such systems: from overfitting and data bias problems to the epistemological problem of induction in predictive inferences. The section demonstrates how the European legislator structured a normative response to technological uncertainty through a risk classification system articulated on four progressive levels: from expressly prohibited practices to high-risk systems, down to limited-risk and minimal-risk systems, each subject to differentiated obligations and controls.